2012
DOI: 10.1055/s-0031-1289680
|View full text |Cite
|
Sign up to set email alerts
|

An Easy Approach for the Synthesis of N-Substituted Isoindolin-1-ones

Abstract: A practical and efficient two-step synthesis of N-substituted isoindolin-1-ones was developed. The one-pot reaction of 2-formylbenzoic acid with amines and dimethyl phosphite proceeds in short time either with conventional heating or microwave irradiation under catalyst-free conditions to afford the corresponding Nsubstituted dimethyl 3-oxoisoindolin-1-ylphosphonates in good yield which, by means of a dephosphonylation reaction with lithium aluminum hydride, give the target N-substituted isoindolin-1-ones in m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 6 publications
1
19
0
Order By: Relevance
“…However, when we carried out the reaction of the cyclic α‐aminophosphonate 9a with LiAlH 4 in anhydrous THF at reflux, the C ‐dephosphonation also occurred, giving the 2‐benzyl‐1,2,3,4‐tetrahydropyrrolo[1,2‐ a ]pyrazine 11 in 65% yield (Scheme ). These results are in agreement with the results obtained for us, when the isoindolin‐1‐one‐3‐phosphonates were reacted under similar reaction conditions.…”
Section: Resultssupporting
confidence: 92%
“…However, when we carried out the reaction of the cyclic α‐aminophosphonate 9a with LiAlH 4 in anhydrous THF at reflux, the C ‐dephosphonation also occurred, giving the 2‐benzyl‐1,2,3,4‐tetrahydropyrrolo[1,2‐ a ]pyrazine 11 in 65% yield (Scheme ). These results are in agreement with the results obtained for us, when the isoindolin‐1‐one‐3‐phosphonates were reacted under similar reaction conditions.…”
Section: Resultssupporting
confidence: 92%
“…The same research group found a useful method for the synthesis of isoindolin-1-one-3-phosphonates from aromatic amines [ 41 ]. The one-pot reaction of aniline 59 with formylbenzoic acid ( 55 ) and dimethyl phosphonate ( 31 ) under the above-mentioned conditions at 90 °C afforded the desired isoindolin-1-one-3-phosphonates 60 in only 14% yields after five days.…”
Section: Reviewmentioning
confidence: 99%
“…Up to now, only three cases were reported for the Kabachnik-Fields-type syntheses of a-aryl-a-aminophosphonates containing an N-benzhydryl group. [22][23][24] In one case the condensation of benzhydrylamine, 1-naphthaldehyde and diethyl phosphite was carried out in the presence of montmorillonite KSF catalyst in a kitchen MW oven. [22] A scandium tris(dodecylsulfate)-catalyzed synthesis of a-aryl-a-aminophosphonates was also described, where triethyl phosphite was applied as the P-component.…”
Section: Introductionmentioning
confidence: 99%
“…[23] Benzhydrylamine was also reacted with formylbenzoic acid and dimethyl phosphite, where 3-oxoisoindolin-1-ylphosphonate was synthesized in a moderate yield. [24] In most cases, these derivatives were synthesized by the Pudovik reaction of a-aryl imines with dialkyl phosphites, [25,26] also providing new information on the peculiar proximity H atoms. [26] In this paper, the synthesis of a-aryl-a-aminophosphonates by the solvent-and catalyst-free Kabachnik-Fields condensation of benzhydrylamine, aromatic aldehydes and dialkyl phosphites was revisited under MW irradiation.…”
Section: Introductionmentioning
confidence: 99%